Pulmonary Tuberculosis Diagnosis Using Artificial Neural Networks - Karam Thanoon; Mohammed Hamdi (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research can detecting the Tuberculosis by using the artificial neural networks, the idea of this research is to design a system that receive the information of patient and give these information to Hamming and Maxnet network which doing the comparison between these information with constant values of human body that stored in network. The system is implemented about many humans (infected and not infected) which has been entered their information to the data base of system, and programmed the system by using visual basic 6.0 with Microsoft access software to build the data base.